The U.K. Business Cycle, Monetary Policy, and EMU Entry - Samiei, Hossein (IMF Working Papers; Working Paper ;, 2000)
In the context of the U.K. government's EMU entry condition of cyclical convergence, this paper (i) provides further evidence suggesting that historically the U.K.'s business cycle has been more volatile than, and relatively independent of, the cycles in the euro-area countries; and (ii) identifies, using a small VAR model, a relatively significant role for monetary policy in explaining these differences. A simulation exercise suggests that if the U.K. interest rates had been more closely aligned with those in the euro area in the 1990s (as they would be if the United Kingdom were to join EMU), output growth might have been less volatile and more correlated with that in the euro area, but inflationary pressures might have persisted.